Pengaruh Literasi Digital Pasien terhadap Aksesibilitas Pendaftaran Online Berbasis Mobile JKN di RSU Bahagia Makassar - Anugerah Nur Adela; Muh Adnan Hudain; Irwandi Rachman; Haeril Haeril; Nur Inayah Ismaniar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Advances in digital technology have driven the transformation of healthcare services, including the implementation of online registration via the Mobile JKN app. However, the app has not yet been utilized effectively because many patients still face limitations in using and operating digital devices, meaning that the potential for digital efficiency has not been fully realized. This study aims to determine the influence of patients’ digital literacy on the accessibility of online registration via the Mobile JKN app at RSU Bahagia Makassar. This study employs a quantitative design of the explanatory research type with a cross-sectional approach. A sample of 77 respondents was selected using purposive sampling, specifically BPJS patients who use the Mobile JKN app for online registration. Data collection was conducted using a 1–5 Likert scale questionnaire. The results of the simple linear regression test indicate that patients’ digital literacy significantly influences the level of accessibility of online registration via the Mobile JKN app, with p = 0.000 and a p-value ≤ 0.05. Based on these findings, it can be concluded that patients’ digital literacy influences the accessibility of online registration via the Mobile JKN app at RSU Bahagia Makassar.